HUBUNGAN PREEKLAMPSIA / EKLAMPSIA DENGAN ANGKA KEJADIAN BAYI INTRAUTERINE GROWTH RETARDATION DI RSUD DR MOEWARDI SURAKARTA PERIODE 1 JANUARI - 31 DESEMBER 2007 - SETIAWAN, AGUS (2008)
This research belongs to analytic research using cross sectional approach. The aim of this research is to know the relationship between preeclampsia/eclampsia and infant intrauterine growth restriction (IUGR) level in RSUD Dr. Moewardi of Surakarta. The research was held on October 2008, then found 80 pregnant woman by using purposive random sampling. Sample divided into two groups that were treatment group and control group, each 40 sample. The result showed that 9 preeclampsia/eclampsia pregnant woman born IUGR babies and 31 preeclampsia/eclampsia pregnant woman did not born IUGR babies. While in control group, found that there are 2 pregnant women born IUGR infants and 38 pregnant woman did not born IUGR baby. By using chi-quadrate test, found that X2 account is 5,165 while X2 table is 3,841 (X2 account is larger than X2table). It can be concluded that there are significant relationship between Preeclampsia/Eclampsia and Infant Intrauterine Growth Restriction Level in RSUD Dr. Moewardi of Surakarta.